EFFECTIVENESS TEST OF THE APPLICATION OF THE BIOPESTICIDE FOBIO IN CONTROL OF BROWN SPOT DISEASE (CURVULARIA SP.) ON RICE PLANTS (ORYZA SATIVA L.) IN RICE FIELDS IN PUTON VILLAGE, JOMBANG REGENCY, EAST JAVA - Ustman Buchori; Sri Wiyatiningsih; Tri Mujoko (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Brown spot (Curvularia sp.) is a plant disease that poses a serious threat to cultivated crops such as rice. This study aims to test the effectiveness of the biopesticide FOBIO in suppressing the intensity of this disease and supporting rice plant growth. The study was conducted in Puton Village, Jombang, using a factorial randomized block design with a combination of FOBIO concentrations (0, 5, and 10 ml/L) and seed soaking times (10, 20, and 30 minutes). The results showed that FOBIO treatment, especially at a concentration of 10 ml/L for 30 minutes, effectively reduced disease intensity and increased plant growth rates. FOBIO has the potential to be an environmentally friendly alternative solution in an integrated pest control system that can be used in the long term.